2007
DOI: 10.1007/s00784-007-0102-7
|View full text |Cite
|
Sign up to set email alerts
|

The recurrent aphthous stomatitis frequency in the smoking cessation people

Abstract: This study was aimed to evaluate the frequency of recurrent aphthous stomatitis (RAS) within the 6-week period after quitting smoking. The study group consisted of 90 subjects. Oral, medical findings and tobacco habits were recorded for all subjects. Nicotine replacement therapy (NRT) and behavioral treatment were applied to some of the subjects by a family physician. All subjects were evaluated for their RAS and periodontal measurements on baseline, 1, 3, 6 weeks by a periodontist. While the subjects were in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 24 publications
0
26
0
9
Order By: Relevance
“…The se re sult co uld sug gest that the wo men who re a li zed that they we re pregnant ga ve up smo king con si de ring the he alth of the ir ba bi es. 13,14 As we men ti o ned in the re sults sec ti on, the smo king ra tes of the smo ker preg nant wo men's hus bands we re sig ni fi cantly hig her than the husbands of the ne ver smo ker preg nant wo men. There may be a hig her risk for the smo ker preg nant women if the ir hus bands a re al so cur rent smo kers.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The se re sult co uld sug gest that the wo men who re a li zed that they we re pregnant ga ve up smo king con si de ring the he alth of the ir ba bi es. 13,14 As we men ti o ned in the re sults sec ti on, the smo king ra tes of the smo ker preg nant wo men's hus bands we re sig ni fi cantly hig her than the husbands of the ne ver smo ker preg nant wo men. There may be a hig her risk for the smo ker preg nant women if the ir hus bands a re al so cur rent smo kers.…”
Section: Discussionmentioning
confidence: 93%
“…12 The per cen ta ge of wo men who had smo ked at any ti me du ring preg nancy was fo und 17% in Si vas Ma ter nity Hos pi tal in 2002. 13 In a recent study car ri ed out in Bur sa Me di cal Fa culty Depart ment of Obs tet ric and Gyne co logy in 2005, the smo king ra te among preg nant wo men was 9.8%. 14 The smo king ra te among preg nant wo men was lower in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Behçet's disease who stopped smoking and, more recently, Marako glu et al found a similar increase in the frequency of RAS following smoking cessation in a cohort without Behçet's disease (5). In the same study, it was noted that patients who used nicotine replacement therapy had a markedly lower frequency of RAS.…”
Section: Ras Has Been Reported To Occur Less Frequently In Smokers (2mentioning
confidence: 90%
“…The hypothesis is that smokers develop mucosal hyperkeratinization, which protects mucosal surface better from the ulceration [21]. Another explanation is that nicotine triggers adrenal steroid production and influences macrophages directly causing decrease in the cytokine production hence decreases the RAS prevalence [24].…”
Section: Etiologymentioning
confidence: 99%